2018
DOI: 10.4254/wjh.v10.i9.549
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of hepatitis C in Egypt and hepatitis B in Mauritania

Abstract: Egypt has one of the highest prevalence rates of hepatitis C virus (HCV) in the world, mostly with genotype 4 that is highly associated with severe fibrosis. As a consequence, hepatocellular carcinoma has become the leading cause of cancer in this country. Mauritania is a highly endemic area for hepatitis B virus (HBV). HBV and HCV could both be iatrogenically transmitted through infected blood products, infected needles, and medical equipment improperly sterilized. Adequate and efficient healthcare and public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 60 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Exposure to infected blood as a consequence of injury means that HCWs (including medical students) are at great risk of infections from the human immunodeficiency virus, HBV, and hepatitis C [8], [9], [10], [11]. Studies showed that HBV demonstrate huge social and economic burden on the society and the authority, with high prevalence rates in some countries around the world, which explain the urgent need to develop more sophisticated infection control procedures training [12], with implementing efficient public health measures and infection control practices to help control the issue [13], moreover, introducing successful public health policies and guidelines will lead to a great decrease and improvement of the HBV status in any community [14].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to infected blood as a consequence of injury means that HCWs (including medical students) are at great risk of infections from the human immunodeficiency virus, HBV, and hepatitis C [8], [9], [10], [11]. Studies showed that HBV demonstrate huge social and economic burden on the society and the authority, with high prevalence rates in some countries around the world, which explain the urgent need to develop more sophisticated infection control procedures training [12], with implementing efficient public health measures and infection control practices to help control the issue [13], moreover, introducing successful public health policies and guidelines will lead to a great decrease and improvement of the HBV status in any community [14].…”
Section: Introductionmentioning
confidence: 99%
“…50,51 Viral factors such as the specific HCVgenotypes and subgenotypes are also important. 52 There has been a growing concern and controversy about an apparent unexpected increase in the number of HCC cases The prevalence of hepatitis B as a risk factor for hepatocellular carcinoma (HCC) in 9 African countries: Egypt, 39 Uganda, 40 Cameroon, 41 Ghana, 42 Nigeria, 43 Kenya, 44 South Africa, 45 and Malawi. 46 developing following direct acting antiviral (DAA) therapy for HCV, as well as higher than expected rates of recurrence following surgical resection in patients receiving DAA treatment.…”
Section: Hepatitis Cmentioning
confidence: 99%
“…It was responsible for 25% of hepatocellular carcinoma (HCC) & 27% of liver cirrhosis cases (Page et al, 2021). Egypt has one of the world's highest rates of hepatitis C virus (HCV) infection (Raad et al, 2018). Genotype 4 is the commonest of the six major HCV genotypes, with 4a as the dominant subtype (Omran et al, 2018).…”
Section: Introductionmentioning
confidence: 99%